I vs. she a comparison of the image of Filipino women in portrayals & self-presentations across traditional mass media & the internet - Alacapa, Mary Lou Garcia (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"Women, as subjects of mass media content, endure as a topic of scholarly inquiry. Many studies have looked at women and the different facets of their image in society. This study does not intend to merely repeat the previous researches on women portrayals; instead, it aims to explore women's self-presentations compare with women portrayals in the traditional mass media and in the Internet. Using method of content-textual analysis, articles about Filipino women were analyzed. The data gathering yielded a total of 333 articles taken from the Philippine Daily Inquirer, Mod, Seventeen and Women's Journal magazines for print; Xanga, Tabulas, Livejournal and Blogger weblogs; and 32 webpages searched through the Yahoo and Google search engines. Findings show that Filipino women have less control over their image in traditional print media than their image in the Internet. Women writers in traditional mass media are still heavily influenced by the concepts of the muted group and hegemony. The image of Filipino women in print still revolves around the basic stereotypes. The image of the nurturing mother is depicted as the ideal in print portrayals and self-presentations. On the other hand, Internet portrayals of Filipino women are more progressive. While print portrayals place more emphasis on women's appearance, web portrayals focus more on the women's achievements rather than their looks. Self-presentations across media vary only slightly. These differences are partly due to the different demographics of Filipino women who choose to write about themselves. While Filipino women in print self-presentations are ideally career-oriented and nurturing mothers, Filipino women in the Internet are students or young professionals who are dedicated to their work."
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman